2013
DOI: 10.1021/jp408664n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Activation of Substrate Templating in Molecular Self-Assembly by Deprotonation

Abstract: Templated assembly of organic molecules constitutes a promising approach for fabricating functional nanostructures at surfaces with molecular-scale control. Using the substrate template for steering the adsorbate growth enables creating a rich variety of molecular structures by tuning the subtle balance of intermolecular and molecule−surface interactions. On insulating surfaces, however, surface templating is largely absent due to the comparatively weak molecule−surface interactions compared to metallic substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…These upright-standing molecules form islands that are shown in Figure 2b. 32 Upon annealing to 580 K, a second structural change is observed. This structural change has previously been assigned to dehalogenation and dimerization of two IBA molecules to form biphenyl-4,4′-dicarboxylic acid (BPDCA, referred to for simplicity as "dimer" in the remainder of this work).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These upright-standing molecules form islands that are shown in Figure 2b. 32 Upon annealing to 580 K, a second structural change is observed. This structural change has previously been assigned to dehalogenation and dimerization of two IBA molecules to form biphenyl-4,4′-dicarboxylic acid (BPDCA, referred to for simplicity as "dimer" in the remainder of this work).…”
Section: Resultsmentioning
confidence: 99%
“…29−31 These achievements have been reviewed in refs 6 and 8, focusing on the relevant experimental and theoretical studies to date, respectively. Despite the considerable progress achieved on metal surfaces, comparatively fewer studies of synthesis on insulating substrates are available in the literature, including reactions on bulk surfaces through Ullmann-type processes, 3,6,19,32 photochemical initiation, 20 and reactions on insulating thin films 18 (see also ref 6 and references therein). Several factors make on-surface syntheses on insulators rather challenging.…”
Section: Introductionmentioning
confidence: 99%
“…An example that is ascribed to this anchoring mechanism is 4-iodobenzoic acid on the (104) cleavage plane of calcite [96], as shown in Fig. 9.8.…”
Section: Increasing the Molecule-surface Interactionmentioning
confidence: 95%
“…The interaction is expected to significantly increase in strength if not only polar molecules are present, but if molecular ions are employed [73,96]. An example that is ascribed to this anchoring mechanism is 4-iodobenzoic acid on the (104) cleavage plane of calcite [96], as shown in Fig.…”
Section: Increasing the Molecule-surface Interactionmentioning
confidence: 98%
“…[20][21][22][23] One way of creating a stable wetting layer on the calcite (10.4) surface has been proposed via the deprotonation of a benzoic acid derivatives. 24,25 In the latter study, Non-Contact Atomic Force Microscopy (NC-AFM) experiments performed at room temperature 25 have revealed that the 2,5-dihydroxybenzoic acid (DHBA) molecules form two ordered phases: one consisting of alternating stripes with different apparent height (a striped phase) and the other, more uniform, made of a network of regular spots (a dense phase). The striped phase has been observed to completely disappear over time at room temperature, while, correspondingly, existing dense phase islands have increased in size and number.…”
Section: Introductionmentioning
confidence: 99%